Women's Reproductive Health for Housewives in the Work Area of the Passo Health Center, Ambon City - Ivy Violan Lawalata; Bellytra Talarima; Lisse Pattipeiluhu (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
Reproductive health for housewives in the work area of the Passo Health Center is carried out based on problems from the partner group, namely low knowledge and minimal information about women's reproductive health, especially cervical cancer and breast cancer as well as skills in practicing or performing the BSE method resulting in low awareness of the importance women's reproductive health, this is shown through the low behavior of early detection carried out by housewives both the IVA test for early detection of cervical cancer and the application of the BSE method for early detection of breast cancer. With the aim of increasing the knowledge, skills and health of housewives in the target group regarding reproductive health, especially cervical cancer and breast cancer as a prevention effort. As well as increasing the knowledge of mothers about basic clinical information on cervical cancer and breast cancer, methods of detection as prevention and treatment methods, the number of mothers who are detected and can be treated. The solutions applied to the above problems are (1). Counseling to increase the knowledge of housewives about women's reproductive health (cervical Ca and breast Ca); (2). perform early detection of cervical cancer and early detection (screening) of breast cancer. The method used for the implementation of the solution is (1). Lectures, questions and answers and discussions both audio (sound) and visual (pictures and video) to increase mothers' knowledge about women's reproductive health; (2). Visual inspection method with acetic acid, also known as visual inspection with acetic acid (IVA test) for early detection of cervical cancer in housewives of the target group; Evaluation is carried out for each implementation of activities to encourage understanding of housewives to behave healthily towards reproductive health.